Asia-Pacific contemporary finance and development - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics, 2019)
Asia-Pacific Contemporary Finance and Development collects a well-informed range of fourteen chapters, investigating banking, finance, production, and consumer sectors that are vital shares of modern economies and definitive drivers of growth in the Asia-Pacific economies. The chapters, authored by internationally renowned and experienced academics, showcase the most updated economic and entrepreneurial dynamism in the Asia-Pacific, a large and thriving region that is recognized as a driving force of innovation and economic growth worldwide. From the TPP and the U.S., to short-term cross-currency basis swap and Japanese government bond markets, and from volatility and risk-taking firms and corporate diversification strategy and the political effects of the Corporate Social Responsibility, to consumption propensity and entrepreneurship, this volume of The International Symposia in Economic Theory and Econometrics explores and investigates contemporary challenges and issues facing the Asia-Pacific economies. For researchers and students of economics and finance, this volume is a fascinating exploration of emerging topics in one the fastest growing economies in the world.